Description Of Age And Bmi In The Hypothermia And Normothermia Group In Caesarea Sectio Patients With Spinal Anesthesia - Jaya Zega, Firman; Mixrova Sebayang, Septian; Kemal Firdaus, Eza (Java Nursing Journal, 2024)
Background: Hypothermia results in increased risk of bleeding, myocardial ischemia, longer post-anesthesia recovery, impaired wound healing, and increased risk of infection. This is due to the influence of anesthetic use, age, nutritional status, and body mass index. The research aims to determine the description of age and BMI in the hypothermia and normothermia groups in caesarean section patients with spinal anesthesia at the Efarina Etaham Pematang Siantar Hospital. Methods: This type of research is descriptive with a cross sectional approach. The study population was all 40 caesarean section patients with spinal anesthesia in September 2023. The research sample used a total sampling method, namely the entire population was the research sample of 40 respondents. Data analysis using univariate analysis. Findings: The results of the research showed that the body temperature of the respondents experienced hypothermia after anesthesia, the majority aged >35 years, all of them experienced hypothermia as many as 11 respondents (100.00%) and the minority of respondents aged <20-35 years as many as 2 respondents (15.38%) and as many as 25-35 years old. 2 respondents (12.50%). Body temperature after spinal anesthesia showed that the body temperature of the respondents experienced hypothermia, the majority of BMI <18.5 or underweight category were 11 respondents (91.67%) and the minority were Normal BMI (BMI 18.5-22.9) as many as 4 respondents (14.29%). Conclusion: Body temperature changes when spinal induction anesthesia is given.